Pengukuran Penyakit Arteri Koroner Dengan Menggunakan Ankle-Brachial Index (ABI) - Sofwan Sofwan (Pusat riset dan Inovasi Nasional, 2023)
Background: Coronary artery disease (CAD) is the main cause of death in the world. In this study we assessed the ankle-brachial index (ABI) as a screening tool for CAD. Methods: Between 2020 and 2023, a large population-based cross-sectional study was conducted on 4,207 new patients referred to Harapan Kita Hospital. The patients underwent selective coronary angiography via a radial artery approach. ABI was calculated for all patients. Researchers compared ABI with coronary angiography results to determine the specificity and sensitivity of ABI as a screening tool. Results: Abnormal ABI was significantly more common in patients with proven severe CAD (893, 54.8%) than in patients with proven mild CAD (33, 4.7%) or no CAD (94, 5.3% ). The specificity of the ABI was 95.3% and the sensitivity was 54.8%. ABI is associated with risk factors such as smoking, male gender, hypertension, diabetes mellitus and dyslipidemia. Conclusion: ABI can be used as a screening test to prevent CAD with a specificity of 95.3%. We need to consider risk factors other than ABI to improve screening sensitivity. Multidimensional scoring systems should consider risk factors and other noninvasive tests in addition to ABI to develop an ideal screening system for CAD